Community Participation in Nutrition Programs to Reduce Stunting: A Case Study in Kediren Village, Blora - Yusup Iswanto, Ahmad; Riyadi, Agus; Kasmuri, Kasmuri (CV. Dyoqu Publishing Management, 2025)
Background:Stunting is a chronic nutritional problem that has long-term impacts on the quality of human resources. Basic Health Research (Riskesdas) data shows that the prevalence of stunting in Indonesia remains high, including in Blora Regency, Central Java, particularly in Kediren Village, which recorded a figure of 22.1%. This situation requires active community involvement in supporting Community Health Center (Puskesmas) nutrition programs as a mitigation effort. Aims:This study aims to describe the form of community participation in the Kutukan Community Health Center nutrition program and identify the factors that influence this participation. Methods:The study employed a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. Informants were selected purposively, including health workers, integrated health post (Posyandu) cadres, village officials, pregnant women, and members of the community with stunted toddlers. Data analysis was conducted interactively using the Miles and Huberman model, supported by triangulation of sources, techniques, and time to ensure data validity. Result:The research results show that community participation manifests itself in the form of ideas, energy, skills, materials, and social aspects. The stages of participation include planning, implementation, utilization of results, and evaluation. Supporting factors for participation include government intervention, free programs, and public awareness, while inhibiting factors include low nutritional knowledge, time constraints due to work, suboptimal communication, and lack of program follow-up. Conclusion:This study concludes that community participation plays a vital role in the success of the stunting reduction program in Kediren Village. To increase the program's effectiveness and sustainability, strategies are needed to strengthen the capacity of cadres, intensify outreach, and strengthen collaboration between health workers, the village government, and the community.